Private metropolis : the eclipse of local democratic governance - Judd, Dennis R.; McKenzie, Evan; Alexander, Alba (Minneapolis : University of Minnesota Press, 2021)
"Examines the complex ecology of quasi-public and privatized institutions that mobilize and administer many of the political, administrative, and fiscal resources of today's metropolitan regions"--
Introduction : shadow governments and the remaking of the American local state / Dennis R. Judd, Evan McKenzie, and Alba Alexander -- City-building capacity and special-purpose authorities : institutions, interests, and the local state / James M. Smith -- Phantom governments : multiple-function special districts as substitutes for municipalities / Evan McKenzie -- Governing Detroit : the withering of the municipal state / Peter Eisinger -- Transportation empires in the New York and Los Angeles regions : from the old to the new politics of governance and development / Steven P. Erie, Scott MacKenzie, and Jameson W. Doig -- Whetting their appetites : privatization schemes and the case of water / Ellen Dannin and Douglas Cantor -- The role of the state in public-private initiatives : lessons from Great Britain / Alba Alexander -- Financing urban infrastructure and services under the new normal : a look at special assessments / Shu Wang and Rebecca Hendrick -- Devolution and debt : financing public facilities in an age of austerity / Rachel Weber, Amanda Kass, and Sara Hinkley -- Building the public city, privately / David Perry and Mary Donoghue -- Conclusion : the Fate of the public realm / Dennis R. Judd, Evan McKenzie, and Alba Alexander.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 08, 2021).
JSTOR
Keywords: Metropolitan government -- United States; Public-private sector cooperation -- United States; Municipal services -- United States -- Finance; Partenariat public-privé -- États-Unis.; POLITICAL SCIENCE -- American Government -- Local; Metropolitan government; Municipal services -- Finance; Public-private sector cooperation; United States; Electronic book